PELINDUNGAN HUKUM NAMA PANGGUNG PUBLIC FIGURE ATAS TINDAKAN PASSING OFF MEREK - Permana, Yoga (JIPRO: Journal of Intellectual Property, 2024)
In the industrial world, a public figure who uses a stage name without giving it legal protection will be prone to causing problems such as being used for personal gain. For example, someone uses the stage name of a public figure to trick consumers so that many of them use the product, even though the product used does not belong to the public figure. The research was conducted using a normative juridical approach using secondary data. Data collection techniques were carried out using literature studies which were analyzed qualitatively. The results obtained from this research are that stage names can be compared to the names of famous people as stated in Article 21 paragraph (2) letter a of Law Number 20 of 2016 concerning Trademarks and Geographical Indications. This article provides legal protection for public figures' stage names from passing off actions carried out by irresponsible people. This article not only prohibits the use of the name of a famous person, but if it is similar, if there are elements that stand out between the trademark and the name of a famous person without the consent of the party concerned, the registration of the trademark must be rejected. There are several legal steps that can be taken by a public figure who feels aggrieved by someone's passing off his/her stage name, such as filing an objection, canceling the brand, suing for compensation, and criminal charges.